2022
DOI: 10.28945/5033
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Online ELT Research in Indonesia During the COVID-19 Pandemic Through the Community of Inquiry Framework

Abstract: Aim/Purpose: This study attempts to provide a thorough review on online English Language Teaching (ELT) research in Indonesia during the COVID-19 pandemic, with the aim of presenting best practices of online ELT classes for the future blended or hybrid learning scenario. To operationalize the “best practices” of online learning, the Community of Inquiry framework was used as the guiding perspective. Background: There is a dearth of research employing a systematic review of English Language Teaching (“ELT”) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…It is still unexplored how MEPs and EZSs attitudes to HL after COVID-19 ended (participant and variable gaps), what reason they need the HL in the new regular (variable gaps), and what the scenarios of HL in EFL during the new normal (finding gaps). The synthesized evidence shows none of the current study, i.e., students' preference (Anabel & Simanjuntak, 2022), teacher's creativity (Arifani et al, 2019), tertiary level education (Çepik et al, 2016), speaking improvement (Criollo-C et al, 2022), learning efficiency (Doghonadze et al, 2021), EFL learner's perception (Bukhari & Basaffar, 2019;Simbolon 2021), mobility (Ghareb & Mohammed, 2019), community inquiry network (Gozali et al, 2022), constructivist approach (Haddad, 2013), character building (Handayani & Utami, 2020), blended learning application (Huong, 2019), ESL Instructor's reflection (Ibrahim & Ismail, 2021), students' role change (Javed et al,2018), assessment (Kamsin & Din, 2015), second language acquisition (Klimova & Pikhart, 2021), academic stress (Mucshini & Siswandari, 2020), learning solution (Nashir & Laili, 2021), productive language skills (Nayman & Bavlı, 2022), English language teacher (Mendes et al, 2020), computer software (Xiang, 2021), teaching speaking (Xiaodong, 2022), contextual Support (Yuan, 2022), and e-learning effectiveness (Zakarneh, 2018).…”
Section: Introductionmentioning
confidence: 62%
“…It is still unexplored how MEPs and EZSs attitudes to HL after COVID-19 ended (participant and variable gaps), what reason they need the HL in the new regular (variable gaps), and what the scenarios of HL in EFL during the new normal (finding gaps). The synthesized evidence shows none of the current study, i.e., students' preference (Anabel & Simanjuntak, 2022), teacher's creativity (Arifani et al, 2019), tertiary level education (Çepik et al, 2016), speaking improvement (Criollo-C et al, 2022), learning efficiency (Doghonadze et al, 2021), EFL learner's perception (Bukhari & Basaffar, 2019;Simbolon 2021), mobility (Ghareb & Mohammed, 2019), community inquiry network (Gozali et al, 2022), constructivist approach (Haddad, 2013), character building (Handayani & Utami, 2020), blended learning application (Huong, 2019), ESL Instructor's reflection (Ibrahim & Ismail, 2021), students' role change (Javed et al,2018), assessment (Kamsin & Din, 2015), second language acquisition (Klimova & Pikhart, 2021), academic stress (Mucshini & Siswandari, 2020), learning solution (Nashir & Laili, 2021), productive language skills (Nayman & Bavlı, 2022), English language teacher (Mendes et al, 2020), computer software (Xiang, 2021), teaching speaking (Xiaodong, 2022), contextual Support (Yuan, 2022), and e-learning effectiveness (Zakarneh, 2018).…”
Section: Introductionmentioning
confidence: 62%
“…It investigated students' perceptions about using peer feedback focusing on the Indonesian context during synchronous and asynchronous periods from 2012 to 2022. SLR methodology uses a systematic procedure to collect, identify, and critically examine available research studies (e.g., articles, conference proceedings, books, and dissertations) (Gozali et al, 2022;Petticrew & Roberts, 2006). The SLR provided the reader with current literature on a topic.…”
Section: Methodsmentioning
confidence: 99%
“…These outcomes contribute to the field of online education by providing support for the belief that adding IMVs into online classrooms to increase instructor presence can contribute to student satisfaction. According to Gozali, Istiqomah & Widiati (2022), The results of their study showed that the application of technology should be combined with clear instruction and task requirements. They added also that Cognitive Presence needs to be fostered through activities that promote problem solving and critical thinking, such as online discussions, problem-or project-based learning, and self-reflection.…”
Section: Course Instructional Materialsmentioning
confidence: 99%